Sendo f(x)=7x=1, então f(12)-f(9) sobre 3 é igual a:
a)-1
b)3
c)5
d)7
Soluções para a tarefa
Respondido por
39
Alternativa D
se f(X)=7x então, f(12)=7x12 = 84 e f(9)=7x9 = 73
f(12)-f(9)= 84-73 = 21
21/3=7
se f(X)=7x então, f(12)=7x12 = 84 e f(9)=7x9 = 73
f(12)-f(9)= 84-73 = 21
21/3=7
Respondido por
30
Sendo f(x)= 7x + 1, então f(12) - f(9) sobre 3 é igual a:
f(x) = 7x + 1
f(12) = 7 · 12 + 1 = 84 + 1 = 85
f(9) = 7 · 9 + 1 = 63 + 1 = 64
![\frac{f(12)-f(9)}{3} = \frac{85-64}{3}= \frac{21}{3} =7 \frac{f(12)-f(9)}{3} = \frac{85-64}{3}= \frac{21}{3} =7](https://tex.z-dn.net/?f=+%5Cfrac%7Bf%2812%29-f%289%29%7D%7B3%7D+%3D+%5Cfrac%7B85-64%7D%7B3%7D%3D+%5Cfrac%7B21%7D%7B3%7D+%3D7)
f(x) = 7x + 1
f(12) = 7 · 12 + 1 = 84 + 1 = 85
f(9) = 7 · 9 + 1 = 63 + 1 = 64
ProfAmaral:
Obrigado!
Perguntas interessantes
Química,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Artes,
1 ano atrás